The Red Thread of the Relationship between Ben Anderson and Pramudya Ananta Toer: A Literary and Cultural Stare - Herdi Sahrasad; Muhammad Ridwan (Budapest International Research and Critics University, 2020)
This study is about the red thread of the relationship between Ben Anderson and Pramudya Ananta Toer: a literary and cultural stare. Ben Anderson expressed his appreciation for the principles and views of Pramudya Ananta Toer that the existence of social and political commitments in arts and literature in Indonesia in the era of movement was more a response to the conditions of the times. Ben Anderson sees Pram's awareness as a 'patterned' writer of socialist realism ', has a strong humanitarian and popular vision, in which under Dutch colonialism, artists and writers feel a responsibility to participate in changing the fate of colonized communities. It can be concluded that they care and commit to the fate of the underprivileged, the oppressed, under-dog. In fact, from the conditions, language, real life and dialectics in the underworld, they discover the reality of humans and society as they are, authentic and inspiring. That is so. Social reality in their lives has shaped the commitment, color and character in working to rediscover humanity, justice and truth in their own way. In the end, it seems that we are restless, disappointed, hurt, angry and looking for humans. In this case, Ben, and Pram God willing, it is not alone!